A Clinicopathological Study of B-catenin in Colorectal Adenomas - Zhelya Abdullah Hamad; Ava Taher Ismael (Advanced Medical Journal)
Background and objectives: Colorectal adenomas are considered benign tumors, which originate from the mucus-secreting colonic epithelium creating polyps that protrude into the lumen of the intestine. B -catenin is a member of the catenin protein family and it has a dual function that controls the coordination of cell-cell adhesion and gene transcription. The aim of this study was to investigate the immune expression of B - catenin in colorectal adenomas and to describe B-catenin correlation with clinicopathological parameters.